TUNTUTAN HAK DALAM PERSIDANGAN PERKARA PERDATA - Rahadi Wasi Bintoro (Jurnal Dinamika Hukum, 2010)
Procedure of private law in Indonesia have experiencing of some growths, for the example is the mechanism of suing which it's not arranged in Het Herzeine Indonesich Reglement, such as class action, legal standing, citizen lawsuit or actio popularis. This article is study to the difference characteristic of suing in procedure of private law in Indonesia. Pursuant to analysis result, the mechanism of ordinary suing is the mechanism suing by the plaintiff to the sued as effect of contempt of court or break a promise which it have generated loss to plaintiff. Class action is the mechanism of suing by numerous plaintiff which it raised by class representative, that representing his own and his group member, with demand in the form of indemnation. Suing of non government organization (NGO) or legal standing is the mechanism of proffering suing by NGO as collision effect or existence of contempt of court which done by the people which arranged in statues. Citizen lawsuit or actio popularis is a suing that raised by citizen to state, as effect of existence of contempt of court, in the form of neglected the civil rights. Its purpose is formed the law order immediately.Keyword: suing, private dispute, plaintiff, sued